2020
DOI: 10.1002/dad2.12060
|View full text |Cite
|
Sign up to set email alerts
|

Small vessel disease lesion type and brain atrophy: The role of co‐occurring amyloid

Abstract: Introduction It is unknown whether different types of small vessel disease (SVD), differentially relate to brain atrophy and if co‐occurring Alzheimer's disease pathology affects this relation. Methods In 725 memory clinic patients with SVD (mean age 67 ± 8 years, 48% female) we compared brain volumes of those with moderate/severe white matter hyperintensities (WMHs; n = 326), lacunes (n = 132) and cerebral microbleeds (n = 321) to a reference group with mild WMHs (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
1
6
0
1
Order By: Relevance
“…In line with the results of previous studies, our results suggest that brain atrophy determines cognitive impairment in elderly subjects with CSVD [ 7 , 53 ]. The relationship between brain atrophy and cognitive impairment is complex and is mediated by several factors including age, WMH load, (strategic) lacunes, CMBs, vascular risk factors and β−Amyloid deposition due to concomitant Alzheimer's pathology [ 54 , 55 ]. A longitudinal imaging study on CSVD patients investigating changes in diffusion and structural imaging described short-term changes in DTI parameters preceding (further) whole-brain atrophy and (progressive) cognitive deterioration [10] .…”
Section: Discussionmentioning
confidence: 99%
“…In line with the results of previous studies, our results suggest that brain atrophy determines cognitive impairment in elderly subjects with CSVD [ 7 , 53 ]. The relationship between brain atrophy and cognitive impairment is complex and is mediated by several factors including age, WMH load, (strategic) lacunes, CMBs, vascular risk factors and β−Amyloid deposition due to concomitant Alzheimer's pathology [ 54 , 55 ]. A longitudinal imaging study on CSVD patients investigating changes in diffusion and structural imaging described short-term changes in DTI parameters preceding (further) whole-brain atrophy and (progressive) cognitive deterioration [10] .…”
Section: Discussionmentioning
confidence: 99%
“…The most common forms are arteriosclerosis and cerebral amyloid angiopathy ( 35 ). However, there is currently limited research on the association between different types of SVD and brain atrophy ( 36 ). This may be the main future SVD research direction.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 , 16 Furthermore, several studies have shown that cerebrovascular disease MRI markers are associated with hippocampal and medial temporal brain volumes. 17 , 18 , 19 , 20 , 21 Despite this, very few autopsy‐based studies have examined the relationship between measures of intracranial atherosclerosis and MRI‐based measures of Alzheimer's dementia.…”
mentioning
confidence: 99%